A Circular Economy Approach to Fish Oil Extraction. Issue 17 (6th May 2019) - Ciriminna, Rosaria; Scurria, Antonino; Avellone, Giuseppe; Pagliaro, Mario
Abstract: Fish oil rich in polyunsaturated omega‐3 fatty acids is extracted in high yield from anchovy filleting waste using d ‐limonene as green biosolvent in a simple solid‐liquid extraction performed by mechanically stirring and maceration followed by limonene removal via evaporation under reduced pressure. As limonene is renewably obtained from waste orange peel, this method closes the materials cycle and establishes a circular economy process to obtain high quality fish oil from biowaste available worldwide in several million t/year amount. Significant economic, social and environmental benefits are anticipated. Abstract : Sustainable Omega‐3! Fish oil rich in polyunsaturated omega‐3 fatty acids can be extracted in high yield from anchovy filleting waste using limonene renewably obtained from waste orange peel as green solvent. The method closes the materials cycle and establishes a circular economy process to obtain high quality fish oil from biowaste available worldwide in several million t/year amount.